Intrahepatic cholestasis of pregnancy: Association with glycaemic control in gestational diabetes. Issue 8 (7th April 2021) - Axelsen, Silja M.; Kampmann, Ulla; Koefoed, Anna S.; McIntyre, David; Ovesen, Per G.; Fuglsang, Jens
Abstract: Aims: The aim of this study was to determine whether the metabolic glucose profile, based on glycaemic control and insulin requirements, was different in women with gestational diabetes mellitus (GDM) and intrahepatic cholestasis of pregnancy (ICP) compared to women with only GDM. Methods: This retrospective cohort study comprised women with GDM and ICP matched with women with only GDM was undertaken at Aarhus University hospital, Denmark, from 2012 to 2019. A total of 46 cases and 184 controls were compared in relation to glycaemic control during pregnancy. Women with GDM and ICP were further divided into subgroups according to the severity of ICP: mild ICP (fasting bile salts 10–39 μmol/L) and moderate/severe ICP (bile salts ≥40 μmol/L). Results: No statistically significant differences were observed in baseline 2‐h oral glucose tolerance test values, second and third trimester HbA1c values, or maximum insulin requirements during pregnancy between women with GDM with and without ICP. Significantly more women with ICP developed preeclampsia during pregnancy: 23.9% (11/46) versus 7.6% (14/184); p = 0.003. Conclusions: This study is the first to address the course of pregnancy in women with GDM with and without ICP in a clinical setting. Under the current treatment guidelines, ICP is not associated with clinically significant changes in glycaemic control in GDM. Significantly more women with both GDM and ICP developed preeclampsia.